Thermal Hydraulic Criteria for Base-Triggered Vapor Explosion - Takahiro ARAI; Yutaka ABE (Journal of Thermal Science and Technology, 2007)
Spontaneous vapor explosion can occur when a layer of high temperature molten material is deposited on a pool of water or on a moist floor. This is called a base-triggered vapor explosion. In order to clarify the micro-mechanism of base-triggered vapor explosions, an experimental apparatus was designed and constructed to observe the base-triggered vapor explosion from the bottom upwards. This experimental apparatus also allowed detailed observation of the microscopic behavior at the interface between the molten material and the water. The experiments used U-Alloy95 as a simulant material. As a result, it was found that water was trapped between molten material and the floor when the molten material droplet was released into the water and covered the floor. Particle imaging velocimetry (PIV) analysis and the digital auto-correlation method were applied to the observation images to evaluate the behavior of the molten material. The upward blowout velocity of the molten material was measured from the images observed from the side of the test section and the ratio of the kinetic energy to the thermal energy of the molten material was estimated from the blowout velocity.